MANAJEMEN PENGOLAHAN NILAI SISWA DI SMA MUHAMMADIYAH 5 RANCAEKEK - Epson Thrismono (Masoem University, 2018)
SMA Muhammadiyah 5 Rancaekek is a high school private school located in West Java Province, Bandung. This school uses Islamic Religion as the main hand of religious education. Which is located at Jl. Raya Rancaekek Majalaya No. 85 Rancaekek, Established in 1976 by the Primary and Secondary Education Section of the Branch of Muhammadiyah Sidoarjo.The research method used in this research is descriptive descriptive method and system development method used to support the preparation of this Final Project report in describing the data flow that is by using Waterfall method or System Development Life Cyle (system development life cycle). The tools used in system design are DFD, data flow level diagram, flow chart (Flow Map), and ER diagram (Entity Relationship).The design of this information system using tools such as Flow Map, Data Flow Diagram, Structure Chart and Diagran ER. The design results are applied in Microsoft Visual Foxpro 9.0 Programming. In this designed system is expected to Minimize the occurrence of duplication of student data and To facilitate the officer to make report selection, pendaftarn and payment.